Proceedings of MOL2NET 2020, International Conference on Multidisciplinary Sciences, 6th Edition 2020
DOI: 10.3390/mol2net-06-06798
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Natural Therapeutics Encapsulated Biopolymeric Okra Mucilage Nanoparticles as Dual ameliorative agent

Abstract: Graphical AbstractAbstract.Among the different types of biomaterials, natural excipients Okra mucilage (MNP) is economic and has the potential for controlled drug delivery. We have synthesized MNPs by co-precipitation method and characterized them by XRD, FESEM, FTIR, UV-Vis spectra and DLS. Despite their potential anti-cancer activity, solubility of curcumin, piperine, thymoquinone is very low rendering its limit in application. We have used MNPs where the natural compounds like MOL2NET, 2020, 6, ISSN: 2624-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Pal (2020) encapsulated curcumin, thymoquinone, and piperine in a nanoparticle system using okra mucilage extract. The results showed that this system had a promising effect on inhibiting the growth of bacteria and cancer cells (Pal, 2020) .…”
Section: Introductionmentioning
confidence: 98%
“…Pal (2020) encapsulated curcumin, thymoquinone, and piperine in a nanoparticle system using okra mucilage extract. The results showed that this system had a promising effect on inhibiting the growth of bacteria and cancer cells (Pal, 2020) .…”
Section: Introductionmentioning
confidence: 98%